Impact of utilities distribution in the population scattering: one analyzes of the African reality -Huambo Angola - Cesar Pakissi (European Regional Science Association (ERSA), 2015)
The migratory phenomenon has been familiar with different realities, where less expectable regions can win or lose its population density influenced by factors whose compression can help to rethinking the forms of urban structure. The numerous studies on population trends and migratory flow the densification of urban centers and related to aspects such as social security, land productivity, life quality, employment and accessibility to socials services that can cause changes in the way population is scattered by territory. This reality is evident in developing countries who face mobility of its labor force in search of better opportunities in the more urbanized locations, leaving marks on economic or in regions that lose population, as well as those who earn. Therefore, realizing the real impact of employment in population distribution, in order to understand the impact that particular activity exercises can be an economic development strategy and ensuring the welfare for many countries in sub-Saharan Africa where 60 percents of the urban population are ?in Slum conditions'. And, Angola is in this reality not only for its geographical context, but, by the existence of numerous factors that systematically attract the population from rural to per-urban areas, increasing the population density of urban centers at the same rate that degrades the life quality. Surprisingly this evidence, few studies have devoted attention to understand the dynamics of population flow and its implications. Around this problematic the problem is: what policies or governance measures can redirect the current urban densification? Has a certain economic factors and urban restructuring impact in the population sprinkling? Or, will the jobs associated with basic services such as education and health, influence in the population grouping to the point of creating new intermediate centers? Or own population density is that it tends to attract these jobs? Considering to these questions, the study aims to estimate the impact of the allocation of public services (education and health) in population distribution, and seeks to understand the interaction between public services and spatial distribution of population. Using a spatial interaction model developed in MatLab, we formulate up five study scenarios of jobs distribution and analyzed data through, of Angola National Development Plan 2013 -2017,. The results are not only a management tool in the urbanization process that is required in locations rapidly growing, as in the case of Huambo city. That as the country's environment of fruit watching a rural exodus that could collapse the sustainability of existing urban scepters, more like also the results are very suggestive to understand the causes of migration and the constraints to the development of centralities.
Keywords: 330; Migration; distribution of public employment; population flow